The Influence of Organizational Culture, Communication and Work Satisfaction on Organizational Commitments: A Case Study of Lecturers at Yayasan Pendidikan Borobudur - Novia, Meita; Faisal, Ahmad (International Journal of Business, Economics and Management, 2021)
This study aims to obtain factual data and information that is valid and true and can be trusted about the influence of organizational culture, communication, and job satisfaction on the organizational commitment of lecturers at the Yayasan Pendidikan Borobudur. This research was conducted using a quantitative research approach, using a survey method, covering survey activities, testing instruments through validity, and reliability testing, as well as collecting and processing research data. The sample in this study was 114 permanent lecturers at the Yayasan Pendidikan Borobudur. The measurement in this study was carried out by giving the value of each question item from all variables. Measuring the value given in each question using the "Likert Scale". Data derived from the distribution of questionnaires carried out an analysis of research requirements, namely: The Goodness of Fit test, the Assessment of Normality test, and the Malahanobis Distance test. Data analysis techniques using Structural Equation Modeling analysis. Based on the results of research analysis: 1) there is an influence of Organizational Culture (X1) on Job Satisfaction (X3) of 0.154 2) There is an influence of Communication (X2) on Job Satisfaction (X3) of 0.109; 3) There is an influence of Organizational Culture (X1) on Organizational Commitment (Y) of 0.669; 4) There is an influence of Communication (X2) on Organizational Commitment (Y) of 0.069; 5) There is an influence of Job Satisfaction (X3) on Organizational Commitment (Y) of -0.111.